Pengaplikasian Teknik Stensil dengan Motif Pucuk Rebung pada Inovasi Busana Etnik Riau - Siti Marizqy Salsabilla; Pipin Tresna Prihatin (JURNAL RUPA, 2021)
The stencil technique is one of the printing techniques in printmaking which is the oldest background design technique. This technique uses a stencil media that is useful as a print barrier on the print media that will paint. This easy way of working using media that can be found anywhere has inspired it to be applied to ethnic dress innovations. Indonesia, which has various ethnic groups, is rich in culture, as well as textile motifs that have their own characteristics. Riau has the pucuk rebung textile motif which is famous for its fusion of Islamic and Malay culture. Pucuk rebung have a philosophical meaning that can be translated into ethnic clothing innovations, one of which is by applying them using the stencil technique.The purpose of compiling this comprehensive study scientific article is to apply the knowledge gained from lectures on Ethnic Dress and Ornamental Design courses, introducing stensil technique as an ornamental technique in fabrics, and develop student creativity as well as improve quality, product competitiveness, added value to ethnic clothing innovation products in preserving the Riau regional culture by using the Project Based-Learning method which can produce permanent knowledge because it provides learning in real situation.